Impact loading of a space nuclear powerplant - Evgeny I. Kraus; Ivan I. Shabalin (Fracture and Structural Integrity)
Preferred formulation of the problem in two space dimensions are described for solving the three fundamental equations of mechanics (conservation of mass, conservation of momentum, and conservation of energy). Models of the behavior of materials provide the closure to the three fundamentals equations for applications to problems in compressible fluid flow and solid mechanics. Models of fracture and damage are described. A caloric model of the equation of state is proposed to describe thermodynamic properties of solid materials with the phase transitions. Two-dimensional problems of a high-velocity impact of a space nuclear propulsion system reactor are solved. High-velocity impact problems of destruction of reactor are solved for the two cases: 1) at its crash landing on the Earth surface (the impact velocity being up to 400 m/s); 2) at its impact (with velocity up to 16 km/s) with the space debris fragments.